Adolescents' experiences of care during childbirth in health facilities in rural Northern Uganda: a mixed-methods study - Udho, Samson (Department of Health and Rehabilitation Sciences, 2025)
Background: Despite the importance of care experience during childbirth, there is a dearth of literature on adolescents' experiences of care during childbirth and how their experiences influence their satisfaction with care and future utilization of healthcare facilities. This study examined adolescents' perceptions of PCMC during childbirth in health facilities in rural northern Uganda and how their perceptions influenced their satisfaction with care and future childbearing intentions (intentions to give birth, give birth in the same facility, and recommend the same facility to a sister or friend), and explored the drivers of adolescents' experiences of care during childbirth. Methods: A mixed-methods study was conducted among 570 adolescents aged 14 to 19 years who gave birth in public health facilities in northern Uganda. Adolescents' perceptions of PCMC were measured using the PCMC tool, satisfaction with care was measured using the Six Simple Questions tool, and future childbearing intention was measured using questions from the Community Survey tool. Qualitative data was collected from 14 purposively sampled participants using in-depth interviews. Quantitative data were analysed using descriptive and regression analyses, while qualitative data were analysed thematically and integrated with quantitative data. Results: The PCMC percentage mean score out of 100% was 62% (SD ± 10.12), and percentage mean scores for sub-scales of dignity and respect was 60% (SD ± 12.05), 59% (SD ± 17.12) for communication and autonomy, and 63% (SD ± 9.92) for supportive care. Adolescents' perceptions of moderate/high PCMC during childbirth were positively associated with being married (AOR = 2.61, 95% CI: [1.01, 6.76]), doing casual labour (AOR = 3.18, 95% CI: [1.52, 6.68]), and having an episiotomy (AOR = 1.88, 95% CI: [1.05, 3.36]). Conversely, five to seven antenatal visits (AOR = 0.52, 95% CI: [0.33, 0.83]), birth companionship (AOR = 0.34, 95% CI: [0.19, 0.60]) and having a newborn with complications (AOR = 0.25, 95% CI: [0.09,0.68]) were negatively associated. The mean satisfaction with the care score was 30.12/42 (SD ± 4.10). Adolescents perceived moderate and high levels of PCMC during childbirth were positively associated with satisfaction with care (β = 4.01, 95% CI [3.14, 4.88], p < 0.001and β = 4.38, 95% CI [2.91, 5.86], p < 0.001 respectively). Most adolescents expressed intentions to have another child (82%), return to the same facility for future childbirth (83%), and recommend the same facility to a sister or friend (85%). Adolescents perceived moderate and high levels of PCMC during childbirth were positively associated with intentions to choose the same facility for the next childbirth (AOR=2.84, 95% CI [1.61, 5.00] and AOR=5.60, 95% CI [1.19, 26.43] respectively) and recommend the facility to a sister or friend (AOR=4.31, 95% CI [2.46, 7.54]). Adolescents had mixed experiences during childbirth, ranging from positive experiences of effective communication, dignity and respect, supportive care, and health facility hygiene to negative experiences of disrespect and abuse, and health facility constraints. Negative experiences were associated with lack of birthing necessities, younger age, and perceived low social status while positive experiences were driven by passive compliance, calm demeanor, relational skills, possession of birthing necessities, cleanliness, and smartness. Conclusion: Adolescents' varied experiences of care during childbirth, influenced by various individual-level factors, resulted in perceptions of moderate PCMC during childbirth. PCMC has the potential to enhance childbirth experience for adolescent mothers, as well as influence their satisfaction with care and future childbearing intentions.